2013
DOI: 10.3324/haematol.2013.087452
|View full text |Cite
|
Sign up to set email alerts
|

BubR1 is frequently repressed in acute myeloid leukemia and its re-expression sensitizes cells to antimitotic therapy

Abstract: ABSTRACT© F e r r a t a S t o r t i F o u n d a t i o n 2 0 1 3 blasts investigated. By performing functional studies both in non-responsive myeloblastic and responsive lymphoblastic cells, we investigated how reconstitution of the SAC and interference with SAC activity translate into response to spindle poison. Using live-cell imaging, retrovirus-delivered inducible knockdown and overexpression, we demonstrate that re-expression of BubR1 in myeloblastic cells confers an improved response to spindle poison. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Mitotic exit can be more efficiently blocked by direct inhibition of APC/C-dependent proteolysis, while mitotic slippage may occur after SAC activation following spindle poison treatment [24-26]. Furthermore, an increase in expression levels of the APC/C substrate protein cyclin B can boost a mitotic block in spindle poison treated cells by attenuating mitotic slippage [10,18,19]. Since synthesis of cyclin B takes place in mitosis in murine and human cells [14,15] we assumed that conserved networks control the strength of a mitotic block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitotic exit can be more efficiently blocked by direct inhibition of APC/C-dependent proteolysis, while mitotic slippage may occur after SAC activation following spindle poison treatment [24-26]. Furthermore, an increase in expression levels of the APC/C substrate protein cyclin B can boost a mitotic block in spindle poison treated cells by attenuating mitotic slippage [10,18,19]. Since synthesis of cyclin B takes place in mitosis in murine and human cells [14,15] we assumed that conserved networks control the strength of a mitotic block.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic polyadenylation leads to poly(A) tail elongation which promotes translation and requires both a hexanucleotide sequence (AATAAA) and a cytoplasmic polyadenylation element (CPE; T 4-5 A 1-2 T) in the 3'UTR of the mRNA [17]. We and others could show that increased cyclin B levels contribute to a mitotic block [18,19]. These findings suggest that the strength of a mitotic block is governed by the cyclin B expression level, which represents an equilibrium between the synthesis and slow degradation of cyclin B [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…Mcl-1-inducible Kasumi-1 cells were grown in the above-mentioned complete medium in the presence of 2 μg/ml puromycin and 2400 μg/ml geneticin (as described elsewhere [26]). Kasumi-1 cells expressing H2B mCherry were grown in the presence of 5 μg/ml blasticidin.…”
Section: Methodsmentioning
confidence: 99%
“…Dominik et al identified that a low expression of BUBR1 affected the sensitivity to antimitotic therapy of many acute myeloid leukemia cell lines (23). However, the relationship between the expression level of BUBR1 and the occurrence of leukemia remains unclear.…”
Section: Sensitivity To Oxidative Stress Was High Inmentioning
confidence: 99%